Analysis of Personal Income Taxation Determinants in Croatia in Long Run: Evidence from Cointegration Analysis - Palić, Irena; Dumičić, Ksenija; Grofelnik, Barbara (Naše gospodarstvo/Our economy, 2017)
Personal income taxation remains an ongoing issue in Croatia. It is used as an important instrument of income redistribution. Moreover, it directly affects pur- chasing power of the working population. Numerous changes have been made in this type of taxation since the establishment of Croatian tax system. The aim of this paper is to analyse possible determinants of personal income taxation in Croatia. After offering brief insight into public finance theory regarding personal income taxation, the structure of personal income taxation in Croatia is explained. The empirical analysis of the determinants of personal income taxation in Croatia is conducted using cointegration analysis. Economic conditions, average monthly wage, and number of taxpayers are used as determinants of personal income tax used in this research. The cointegration analysis is conducted using monthly data from January 2008 to February 2016. The results of the research show a statistical- ly significant negative impact of economic conditions and statistically significant positive impact of average monthly wage and number of taxpayers on personal income taxation in long run, what is in line with economic and public finance theory.